Principales agentes bacterianos en la Mastitis Bovina - Quispe Peña, Katiana Scarlet (2022)
Currently, bovine mastitis is one of the main diseases that causes a great impact on animal production, due to the inflammatory response in the mammary glands. It is characterized by the invasion of pathogenic microorganisms that are outside the udder and enter the glandular duct. Most incidences of mastitis cases are of microbial origin and the degree of infection depends on the exposure of the teats to the mammary pathogens. For this reason, hygienic measures, fundamentally during the handling of the milking process, are important since they reduce the probability of contamination of the teats with pathogenic organisms, whose main gateway to the mammary gland is the teat canal. For the development of this investigative work, an extensive bibliographic review was made in books, magazines and scientific articles on the subject. The research aims to identify the main bacterial agents causing bovine mastitis. This pathology, due to the degree of inflammation and local lesions, can be classified into "Clinical mastitis" and "Subclinical mastitis". Approximately more than 100 species of pathogens have been found that trigger mastitis, among the main ones we have: Streptococcus dysgalactiae, Streptococcus uberis, Streptococcus agalactiae, Staphylococcus epidermidis, Staphylococcus aureus and Corybacterium pyogenes, the main route of entry to the gland being the teat canal. In conclusion, we have that sanitary measures within cattle considerably decrease the regularity of clinical and subclinical mastitis in cattle herds.